2017
DOI: 10.1016/j.ijid.2016.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ledipasvir/Sofosbuvir with and without Ribavirin in Patients with Chronic Hepatitis C Virus Genotype 1 Infection: a meta-analysis

Abstract: This meta-analysis suggests that LDV-SOF based therapy is a safe and effective treatment for patients with GT 1 HCV. The addition of RBV to LDV-SOF may increase toxicity without achieving improved efficacy. However, due to the relatively small sample sizes and moderate risk of bias of included studies, large-scale and high-quality clinical research is still needed to confirm the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“… 4 , 5 , 6 Lower rates of effectiveness were reported in urban patients in minority racial/ethnic groups. 7 Thus, the advent of newer direct-acting antivirals (DAAs) that could be administered over 8 to 12 weeks with few significant adverse effects 8 , 9 and sustained virologic response of 93% to 99% across different target populations and treatment regimens 10 , 11 , 12 was considered a substantial breakthrough in treating HCV. 13 …”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 , 6 Lower rates of effectiveness were reported in urban patients in minority racial/ethnic groups. 7 Thus, the advent of newer direct-acting antivirals (DAAs) that could be administered over 8 to 12 weeks with few significant adverse effects 8 , 9 and sustained virologic response of 93% to 99% across different target populations and treatment regimens 10 , 11 , 12 was considered a substantial breakthrough in treating HCV. 13 …”
Section: Introductionmentioning
confidence: 99%
“…The adverse event may be related to certain drugs. Tao et al reported significant increase in the overall AE and serious AE rates when adding RBV to the LDV/SOF dual therapy . This provide another evidence against using RBV with other therapeutic regimens.…”
Section: Discussionmentioning
confidence: 95%
“…Although the meta‐analysis about the role of RBV in the regimen was not done based on the stratification of subpopulation with different viral loads, the combination of all three high‐potency DAAs might have similar effects and explain the unnecessary role of RBV in the regimen. Similarly, a recent meta‐analysis investigating the efficacy of LDV and SOF with or without RBV found that adding RBV to this regimen neither improved the viral response nor decreased the virologic breakthrough . Furthermore, Mizokami et al reported that adding RBV to the LDV/SOF decreased the SVR 12 from 100% to 91.7% among treatment‐naïve patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our results showed that a regimen of SOF and NS5A inhibitors without RBV for 12 weeks could be sufficient to ensure the effective treatment of more than 93% of liver recipients. The response rates to DAA combination therapy in LT patients were similar to those observed in the nontransplanted population . According to these findings, LT recipients should not be considered as a “difficult‐to‐treat” population.…”
Section: Discussionmentioning
confidence: 99%